The Impact of Social Media on Consumer Shopping Habits among Teenagers - Sugiyono Sugiyono; Daru Putri Kusumaningtyas (Oikonomia : Journal of Management Economics and Accounting, 2024)
The development of social media has changed shopping habits, especially among teenagers who are the digital native generation. This study aims to examine the influence of social media on teenagers' consumption behavior, focusing on the role of influencers, the Fear of Missing Out (FOMO) phenomenon, and the contradiction between environmental awareness and the tendency to follow fast fashion trends. Social media, particularly platforms such as Instagram, TikTok and YouTube, have become a major factor influencing teenagers' shopping decisions, where they feel compelled to follow trends promoted by influencers or celebrities. FOMO is a key driver that makes teens feel compelled to buy the latest products to avoid feeling isolated. However, although many teenagers are aware of the importance of sustainability, they remain trapped in the habit of fast fashion that offers cheap products with rapidly changing designs. This research uses a qualitative approach with a case study method, involving in-depth interviews, Focus Group Discussions (FGDs), participatory observation, and document study. The results show that social media not only shapes teenagers' shopping habits, but also reinforces social norms that link consumption with social status. This research provides insights into the dynamics of teenagers' consumption in the digital era, especially related to the contradiction between the desire to be more eco-conscious and the urge to follow consumptive trends